Amazonian soil fungi are efficient degraders of glyphosate herbicide; novel isolates of Penicillium, Aspergillus, and Trichoderma - Correa, L. O.; Bezerra, A. F.M.; Honorato, L. R.S.; Cortêz, Ana Cláudia Alves; Souza, J. V.B.; Souza, E. S. (Brazilian journal of biology = Revista brasleira de biologia, 2021)
Pesticide residues that contaminate the environment circulate within the hydrological cycle can accumulate within the food chain and cause problems to both environmental and human health. Microbes, however, are well known for their metabolic versatility and the ability to degrade chemically stable substances, including recalcitrant xenobiotics. The current study focused on bio-prospecting within Amazonian rainforest soils to find novel strains fungi capable of efficiently degrading the agriculturally and environmentally ubiquitous herbicide, glyphosate. Of 50 fungal strains isolated (using culture media supplemented with glyphosate as the sole carbon-substrate), the majority were Penicillium strains (60%) and the others were Aspergillus and Trichoderma strains (26 and 8%, respectively). All 50 fungal isolates could use glyphosate as a phosphorous source. Eight of these isolates grew better on glyphosate-supplemented media than on regular Czapek Dox medium. LC-MS revealed that glyphosate degradation by Penicillium 4A21 resulted in sarcosine and aminomethylphosphonic acid.